Sexual knowledge of premarital pregnant adolescents in Raudhatus Sakinah - Amaran, Safiya (2011)
Introduction: The most challenging aspect of adolescence is sexual and reproductive health, as it is the area that poses the greatest difficulty in maintaining adolescents’ health. Knowledge alone has not been shown to affect adolescent’s behavior, nevertheless it is one of the most important factor that affect their reproductive health. The prevalence of premarital pregnancy among adolescents in Malaysia is increasing, thus this issue can’t simply be ignored. Objectives: To determine the sexual knowledge and identify the factors related to sexual knowledge of premarital pregnant adolescents in Raudhatus Sakinah. Method: This is a cross sectional study using a self administered validated questionnaire. Study samples were from Raudhatus Sakinah institution in Kelantan, Johor and Penang where all eligible and consented individuals were included via purposive sampling due to limited samples (n=33). The profiles were analyzed as descriptive statistics namely mean (SD) and frequency (%). The dependent variable was the knowledge score which was analyzed as numerical variable. The factors related to the sexual knowledge were analyzed using simple linear regression for univariable analysis and multiple linear regression for multivariable analysis. Results: The mean (SD) age of first coitus is 16.3(2.0) years and the mean (SD) age of first pregnancy is 17.1(1.4) years. Forty two percents had history of being raped. Eighty two percents are not willing to discuss sex with their parents. Ninety seven percent of respondent watched pornography. Majority of them has good knowledge on reproductive organs but poor knowledge on details of pregnancy. Knowledge on XIII HIV was better than other sexually transmitted diseases. Media, teacher and friends are their main source of sexual knowledge. For every year increase in age at first coitus, the knowledge increased by 0.80(0.12,1.46) units. For each year of increase in age of partner at the first coitus of the girl, the knowledge score changed by -0.47 (-0.79,-0.15) units. The knowledge score of premarital pregnant adolescent increase by 14(6.59,21.42) units among those who had watched pornography compared to those who did not watch. The knowledge score would increase by 3.80(1.24,6.34) units for premarital pregnant adolescent with history of rape compared to without history of rape. Conclusions: The sexual knowledge of premarital pregnant adolescents in Raudhatus Sakinah is good. The sexual knowledge was significantly related to their age at first coitus, history of rape, age of partner at first coitus of the girl and watching pornography.